A Complicated Urinary Bladder Diverticulum Herniation: A Case Report - Parajuli, Santwana; Sharma, Prakash; Gyawali, Merina; Lalchan, Subita; KC, Subash; Acharya, Ganesh Bhakta; Thapa, Niraj; Tiwari, Prabhat Kumar; Poudel, Ramesh (Nepalese Journal of Radiology, 2018)
Urinary bladder diverticulum presenting as an inguinal hernia is an uncommon condition found in about 1-5% of inguinal hernia. Long standing increase of the intravesical pressure resulting from urinary bladder outlet obstruction can cause both secondary bladder diverticula and groin hernias. We present a case of urinary bladder diverticulum herniating through the left inguinal canal, which was confirmed by micturating cystourethrogram. Although these conditions are usually, diagnosed intraoperatively, radiological diagnosis still holds its utmost importance to improve the overall management.